Practicing strategy text and cases - Paroutis, Sotirios (SAGE, 2013)
Practising Strategy is a groundbreaking new textbook focusing wholly on the cutting-edge Strategy as Practice approach, which considers strategy not only as something an organisation has but something which its members do.